Diffeomorphisms of foliated manifolds - Abdishukurova, G. M.; Narmanov, A. Ya. (Methods of Functional Analysis and Topology, 2021)
The set Diff(M) of all diffeomorphisms of a manifold M onto itself is the group related to composition and inverse mapping. The group of diffeomorphisms of smooth manifolds is of great importance in differential geometry and in analysis. It is known that the group Diff(M) is a topological group in compact open topology. In this paper we investigate the group Diff_F(M) of diffeomorphisms foliated manifold (M,F) with foliated compact open topology. It is proven that foliated compact open topology of the group Diff_F(M) has a countable base. It is also proven that the group Diff_F(M) is a topological group with foliated compact open topology. Also some one-parameter subgroups of the group Diff_F(M) are found and studied for the foliations generated by special submersions. Множина Diff(M ) всіх дифеоморфізмів многовиду M є групою відносно композиції та взяття оберненого і топологічною групою в компактно-відкритій топології. Групи дифеоморфізмів гладких многовидів мають велике значення в диференціальній геометрії та аналізі. У цій роботі досліджується група дифеоморфізмів шаруватого многовиду з розшарованою компактно-відкритою топологією. Показано, що ця топологія має зліченну базу. Знайдені деякі однопараметричні підгрупи групи Diff(M ) і досліджені для шарувань, породжених спеціальними субмерсіями.